ASSESSMENT OF SUSTAINABLE TOURISM IN THE COUNTY OF KOUHDASHT (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Kouhdasht county in the lorestan province is plain land among Zagros mountains And is located between two rivers Seymare and Kashkan. Considering to this excellent position has varied climate, watery rivers, forests and green pastures; Also with transhistorical civilization have been species of ancient and historical monuments And has great potential for tourists attract. But despite plenty of natural and historical attractions, Has not gained much success in tourists attracting. The research Methodology is descriptive-analytic. Data collection mehtod is in the form of document studies. The purpose of this study is evaluate the potentials of the historical, cultural and natural Kouhdasht couny That is facilitator for achieve to sustainable tourism. Due to the breadth and diversity of the natural attractions of county Kouhdasht just is discussed about shirez valley. In reviewing the potential of historic city to be introduced some rock-image of caves (Mir Malas, Homian and Doushe) Sorkh dom of Laki and Lorry archaeological sites, Kalmakareh cave (as one of the world's treasures greatest that discovered), and bronze in the county Kouhdasht. In the study of cultural potentials mentioned to Ashura ceremony and Holy Muhammad; That each of these factors can help to county tourism development. Then is discussed about the weak points of couny for achieve to sustainable development of tourism